Teaching Styles, Performance, and Development Needs of a Junior High School Faculty in Catholic Schools of the Philippines - Joseph Refugio; Sheila Soledad Dalumpines (Journal of Elementary and Secondary School, 2025)
This study addresses a critical issue in the context of Catholic schools in Zamboanga del Norte, Philippines: the relevance of faculty development programs in preparing teachers to meet the demands of a rapidly changing educational environment and the new generation of learners. As the education landscape evolves, it is essential to design holistic and relevant faculty development initiatives to adequately prepare educators for new challenges, including those related to globalization and the VUCAD (Volatility, Uncertainty, Complexity, Ambiguity, and Digitalization) environment. The study specifically focuses on a population consisting of seven school administrators serving as principals, sixty-one teachers, and 1,188 Grade 9 and 10 students from seven Catholic schools. The research objective is to design an integrated and relevant faculty development program by examining teachers’ teaching styles, performance, and professional development needs. A descriptive survey was employed to gather data from all the relevant stakeholders. The results revealed that Junior High School faculty consistently demonstrated six distinct teaching styles, with administrators and faculty perceiving these styles as always present, while students rated them as often demonstrated. Faculty performance was evaluated as very good, and while development needs were identified, they were considered occasional and not significantly detrimental to instructional effectiveness. The study concludes that faculty members exhibit competence and adaptability with minimal development needs. Based on these findings, this study proposes a faculty development program specifically designed to address Catholic high school educators' unique needs in the province.